2018
DOI: 10.1177/1729881418767310
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive brain–computer interface approach for predicting motion intention of activities of daily living tasks for an upper-limb wearable robot

Abstract: Brain-computer interfaces are emerging as an important research area and are intended to create an understanding between a computer and the human brain to ensure that robot-human interactions become more intuitive and userfriendly. However, encoding of brain information to derive the intended motion of the user in real time continues to present a problem with respect to the control of wearable robots with multiple degrees of freedom. In this study, a new approach to control several degrees of freedom in a wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Next, the development of brain simulation software is 14.3% [ 49 , 50 , 51 ], and the development of hybrid architectures (using brain computing interfaces supported by neuromorphic processors) accounts for 14.3% [ 52 , 53 , 54 ]. The development and improvement of brain computing interfaces was 9.5% [ 55 , 56 ], as was analysis and database storage through machine learning [ 57 , 58 ]. Finally, 4.8% was shown for the design of neuromorphic processors [ 59 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Next, the development of brain simulation software is 14.3% [ 49 , 50 , 51 ], and the development of hybrid architectures (using brain computing interfaces supported by neuromorphic processors) accounts for 14.3% [ 52 , 53 , 54 ]. The development and improvement of brain computing interfaces was 9.5% [ 55 , 56 ], as was analysis and database storage through machine learning [ 57 , 58 ]. Finally, 4.8% was shown for the design of neuromorphic processors [ 59 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Time series input data were also applied with damping neurons in the adaptive neuron network controller for force control of robotic manipulators in unknown environments to consider the velocity and acceleration terms and effectively compensate for the unknown dynamics of the environment [42]. In addition, a time-delay feature matrix is used to provide inputs for neural networks and support vector machine-based classifiers, which collect the dynamic characteristics of EEG signals for motion intention prediction in [43]. Furthermore, the authors in [44] confirmed that the convolutive architecture with dynamic information as input is more accurate and robust than recurrent networks in longitudinal vehicle dynamics modeling.…”
Section: B Comparison Resultsmentioning
confidence: 99%
“…In this paper, SVM is used for classification of multi-class (MI) EEG signals [44]. In proposed approach, different parameters can be assigned appropriate values for improving its performance [45]. The values of regularization parameter (C), gamma ( ) and degree of kernel (d) are selected to control the trade-off between number of non-separable points and complexity of algorithm.…”
Section: Support Vector Machinementioning
confidence: 99%